Energy analysis for onsite and offsite suburban wastewater - Omojaro, Peter A. (My University, 2011)
The environmental consequence of meeting the planet's energy requirements has shown that biological degradation of organic constituent from wastewater does not only produces biogas. It also produces flammable methane that has 21 times more global warming potential or greenhouse effect than carbon dioxide. This becomes a loss of potential renewable energy when it is flared. This study investigates recoverable energy from cassava wastewater and effect of unrecovered onsite (not from treatment plant) wastewater energy. Sludge from both onsite untreated and offsite treated wastewater from a cassava processing station in a sub urban community of Nigeria was analyzed. The result shows that the offsite treatment has a methane potential of 27.428 m3/day compared to the onsite methane emission potential with 17.807 m3/day. The onsite 17.807 m3/day of methane is equivalent to 0.126 kgCH4/year of emitted methane base on industrial procedure standards by the IPCC (2006) guidelines for national greenhouse gas inventories. An additional 54.03% of methane will be recovered if the onsite emissions were to be captured. At an emission efficiency of 0.025 kgCH4/kg COD, the untreated wastewater indicates a potential contribution to the greenhouse effect. A mathematical model analysis was presented for ease in determining the amount of methane emitted from the untreated wastewater. This study support suggested methodologies and previous work comparing anaerobic offsite methane potential and untreated wastewater methane emission potentials along with its greenhouse effects. © 2010 Springer Science+Business Media B.V.
Keywords: Emission factor; Energy recovery; Greenhouse gas; Methane; UASB; Wastewater